Improving the hydrogen-adsorption properties of a hydroxyModified MIL-53(A1) structural analogue by lithium doping - Himsl, Dieter; Wallacher, Dirk; Hartmann, Martin (Angewandte Chemie International Edition, 2009)
Lithium makes the difference: A simple strategy for the synthesis of lithium-doped porous metal–organic frameworks (MOFs) is developed (see structure; C black, O red, AlO6 blue octahedra), thus paving the way for the facile preparation of lithium-doped MOFs. Moreover, the significant increase in hydrogen adsorption predicted by theoretical calculations is observed.<br
Keywords: Microporous materials; Doping; Adsorption; Lithium; Hydrogen